Pengaruh Sale Promotion dan Store Atmosphere terhadap Impulsive Buying dengan Positive Emotion sebagai Variable Intervening pada Konsumen Matahari Department Store Yogyakarta - Oktamia Asri Ivo; Henny Welsa; Putri Dwi Cahyani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
There is knowledge about the analysis of the influence of sales store atmosphere and sales promotion on impulse buying and positive emotion in Matahari Department Store Yogyakarta. Non-probability sampling method and purposive sampling technique using Matahari Department Store consumers as many as 100 consumers as respondents. The questionnaire which is the instrument in this study was analyzed using SPSS 25. The researcher took the result that positive emotion was not positively influenced by sales promotion. Positive emotion is positively influenced by store atmosphere. Impulse buying is not positively influenced by sales promotion. Impulsive buying is also not positively influenced by the store atmosphere. Meanwhile, impulsive buying is significantly influenced by the positive emotion variable. Keywords: Sale Promotion, Store Atmosphere, Positive Emotion, Impulsive Buying